A Critical Analysis of Sustainability Reporting in Indonesian Islamic Banking Using Global Reporting Initiative Standards - Dewi Reni; Rido Muhamad Ridho Irza Al Hakim; Muklis (Academic Bright Collaboration, 2026)
Purpose – This study analyzes the breadth of sustainability reporting among Indonesian Islamic commercial banks following the implementation of Financial Services Authority Regulation (POJK) No. 51/POJK.03/2017. Methods – The study employs qualitative content analysis, supported by descriptive statistics, of the 2022 sustainability reports of six Islamic commercial banks. Using a predefined coding sheet, 23 GRI-related aspects were assessed at the aspect level through binary scoring (1 = disclosed; 0 = not disclosed). The findings were interpreted using legitimacy theory and stakeholder theory. Findings – Sustainability disclosure remains uneven across categories. Social disclosure is the most extensive, averaging 5.00 of 8 aspects disclosed (62.5%), followed by environmental disclosure at 4.33 of 11 aspects (39.4%) and economic disclosure at 1.67 of 4 aspects (41.7%). All sampled banks disclosed economic performance and employment-related aspects, whereas indirect economic impacts, biodiversity, equal remuneration, and labor grievance mechanisms were not disclosed. Research implications – The study is limited to one reporting year, six banks, and a single-coder design; therefore, it captures disclosure breadth rather than long-term trends or disclosure quality. Nevertheless, it extends the literature by showing that regulatory adoption does not automatically produce comprehensive GRI-aligned disclosure. Originality – This article offers an aspect-level map of sustainability disclosure in Indonesian Islamic banking and explains selective disclosure patterns through legitimacy and stakeholder perspectives. Unlike prior GRI-based studies in Islamic banking that mainly rely on aggregate disclosure indices, this study maps disclosure at the aspect level to show which themes remain absent after regulatory adoption.